Optoelectronic investigation of Cu2FeSnS4 quaternary functional photodiodes with IR detection capabilities - Koc, Mumin Mehmet; Dere, Aysegul; Ozdere, Alper; Al-Sehemi, Abdullah G.; Coskun, Burhan; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier, 2021)
Cu2FeSnS4 semiconductor used in the preparation of quaternary photodiodes was synthesized using hydrothermal synthesis. The nanoparticles were then spin coated on a silicon substrate. Nanoparticles were characterized using SEM and EDX where nanoparticles in granular form were seen. Optoelectronic properties were assessed using UV spectra throughout which bandgap energies were calculated. The band gap energy of Cu2FeSnS4 semiconductor was found as 1.22 eV. I - V and I - t characteristics illustrate that Al/p-Si/Cu2FeSnS4/Al heterojunction photodiodes were responsive to daylight and infrared light. Ideality factor, barrier height, saturation current, and photoresponse values were calculated using I - V and I - t data. The ideality factors were calculated as 5.14 and 5.61 for daylight and infrared light (IR) illuminations, respectively. Electrical properties of diodes were checked using C - V and G - V analysis. It was seen that the electrical properties of photodiodes strongly depend on AC signal frequency. Our assessment revealed that frequency related electrical behavior is originated from interface states. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Cu-2 FeSnS4; Quaternary photodiodes; Photodetectors; IR detectors